Fawatih As-Suwar : Pembuka Komunikasi dalam Al-Qur’an - Irdan, Alfiani; Sohrah, Sohrah; Miswar, Andi (Hamalatul Qur'an : Jurnal Ilmu Ilmu Alqur'an, 2025)
This study aims to examine the fawatihus suwar in the Qur'an as an important element in establishing divine communication. This research uses a descriptive qualitative approach based on literature analysis, referring to tafsir books, linguistics texts, academic journals, and other scholarly sources. The main focus of the study is to explain the function of the surah openings in introducing themes, capturing attention, and reinforcing the overall message of the surah. The analysis results show that fawatihus suwar play a significant rhetorical role, including conveying symbolic meanings, strengthening the emotional connection with the audience, and introducing the Qur'anic narrative structure. This study contributes to the development of understanding the linguistic dynamics and communication functions within sacred texts, while also enriching the academic literature on Qur'anic studies.